A teaching experience using a flight simulator: Educational Simulation in practice - Sergio Ruiz; Carlos Aguado; Romulado Moreno (OmniaScience, 2014)
The use of appropriate Educational Simulation systems (software and hardware for learning purposes) may contribute to the application of the "Learning by Doing" (LbD) paradigm in classroom, thus helping the students to assimilate the theoretical concepts of a subject and acquire certain pre-defined competencies in a more didactical way. The main objective of this work is to conduct a teaching experience using a flight simulation environment so that the students of Aeronautical Management degree can assume the role of an aircraft pilot, in order to allow the students understanding the basic processes of the air navigation and observe how the new technologies can transform and improve these processes. This is especially helpful in classroom to teach the contents of the Single European Sky ATM Research (SESAR) programme, an European project that introduces a new Air Traffic Management (ATM) paradigm based on several relevant technological and procedural changes that will affect the entire air transportation system in the short and medium term. After the execution of several activities with a flight simulator in the classroom a short test and a satisfaction survey have been requested to the students in order to assess the teaching experience.